The Role of Farmers Groups Towards Increasing the Productivity of Rice Business in Semarang City - Khilmi Nur Cholisoh Nur Cholisoh (Perum BULOG, 2023)
Farmer groups help to manage the farm and overcome farming problems, as well as a place for the learning process for farmers to carry out farming activities optimally. This study analyzed the correlation between farmer groups’ role in rice farming productivity in Mijen District, Semarang City. The correlation test was carried out using the chi-square test. Data collection methods used questionnaires and in-depth interviews. The sampling technique used was purposive sampling based on farmer groups who were active and less active in organizations. The sample collection method used the census method (complete enumeration), where all members of the farmer group based was interviewed, which amounted to 110 people. The role of the farmer group as a learning class, a vehicle for cooperation, and a production unit in Mijen District, Semarang City, was classified as very good. The productivity of rice farming of farmer group members has increased after joining the farmer group. There was a significant correlation between the role of farmer groups as a learning class, cooperation model, and also production unit with the productivity of rice farming. All stakeholders, including the government, community institutions, and farmers, are expected to take advantage of the factors that have been identified to improve farm productivity.